Estratégias de promoção de saúde com portadores de hanseníase no município de Paracatu -MG - Lima, Michelle Faria (2009)
It is waited that the educational practice in health when based in the Health Promotion, favor the transformation possibility in the conditions of the individuals' life and population groups. Historically, the strategies of Leprosy control in Brazil went through successive transformations. The current strategies consist of the decentralization of the service of the Reference Center for the Teams of the Health Program of the Family installed in most of the Brazilian municipal districts. Leprosy is a communicating diseases considered as a public health problem in Brazil and in several other countries. The World Health Organization targeted the global elimination of the disease as a public health problem until the year 2000, measured by a prevalence smaller than 1/10,000 inhabitants. Eight years thereafter, Brazil did not achieve the target, being the only country in Latin America still having leprosy as a public health problem. The Brazilian State of Minas Gerais is classified as High Transmission Risk for leprosy, given its average Detection Coefficient varying, in the last seven years, from 2 to 4/10,000 inhabitants. The municipality of Paracatu-MG is one of the main contributors to this reality. Classified as hyper endemic, Paracatu presented Detection Coefficient varying, between 2000 and 2005, from 11.8 to 8.6 cases/10,000 inhabitants. Its classification decreased from Very High Risk (up to 2005) to High Risk from 2006. This descriptive study was aimed at knowing the education and the procedures of health professionals, in relation to the detection, treatment and referral of leprosy patients, as well as identifying the existence of activities and strategies for these patients’ Health Promotion. A secondary-data epidemiological survey, of the main epidemiologic and operational indicators of the disease in Brazil, in Minas Gerais and in Paracatu (between 2000 and 2007), was performed. Three questionnaires were elso applied to health professionals from the Leprosy Reference Centre and the Family Health Units, as well as to patients in treatment. We conclude that it lacks both information on the disease for the affected population and knowledge, on advice measures and health promotion strategies for leprosy patients, for the health professionals. Because there is no active search for new cases, epidemiological surveillance only identify the few cases that, despite stigmatization, come spontaneously to the health care units, perpetuating an underreporting reality. We recommend the de-centralization of the leprosy service, community participation in decision making, and educational and health promoting programmes for leprosy patients. Such strategies will facilitate population empowering in relation to their health determinants and to their access to health services, fundamental condition to achieve the necessary de-stigmatization of the disease and improvement in quality of life of leprosy patients.